The Flying King: the novelistic Alexander (Pseudo-Callisthenes 2.41) and the traditions of the Ancient Orient - Konstantakos, Ioannis M. (Classica - Revista Brasileira de Estudos Clássicos, 2020)
The story of Alexander’s flight is preserved in early Byzantine versions of the Alexander Romance (codex L, recensions λ and γ) but is already mentioned by Rabbi Jonah of Tiberias (4th century AD) in the Jerusalem Talmud. The narrative must have been created between the late Hellenistic period and the early Imperial age. Although there are differences in details, the main storyline is common in all versions. Alexander fabricates a basket or large bag, which hangs from a yoke and is lifted into the air by birds of prey; Alexander guides the birds upwards by baiting them with a piece of meat fixed on a long spear. The same story-pattern is found in oriental tales about the Iranian king Kai Kāūs and the Babylonian Nimrod. Kai Kāūs’ adventure was included in the Zoroastrian Avesta and must have been current in the Iranian mythical tradition during the first millennium BCE. It is then transmitted by Medieval Islamic authors (Ṭabarī, Bal‘amī, Firdausī, Tha‘ālibī, Dīnawarī), who ultimately depend on Sasanian historical compilations, in which the early mythology of Iran had been collected. The story of Kai Kāūs’ ascension is earlier than Pseudo-Callisthenes’ narrative and contains a clear indication of morphological priority: in some versions the Persian king flies while seated on his throne, which reflects a very ancient and widespread image of royal iconography in Iran and Assyria. Probably Alexander’s aerial journey was derived from an old oriental tradition of tales about flying kings, to which the stories of Kai Kāūs and Nimrod also belonged. The throne had to be eliminated from Alexander’s story, because the episode was set during Alexander’s wanderings at the extremities of the world. The Macedonian king had therefore to fabricate his flying vehicle from readily available materials. Later, after the diffusion of Pseudo-Callisthenes’ romance in the Orient, the tale of Alexander’s ascension might have exercised secondary influence on some versions of the stories of Kai Kāūs and Nimrod, regarding specific details such as the use of the bait.